Physical Appearance Perfectionism: Psychometric Properties and Factor Structure of an Assessment Instrument in a Representative Sample of Males - Rica, Robin; Solar, María; Moreno-Encinas, Alba; Foguet, Sara; Compte, Emilio Juan; Sepúlveda, Ana Rosa (Frontiers in Psychology, 2022)
Perfectionism is a multidimensional construct with both positive and negative aspects. Recently, the concept of appearance-oriented perfectionism has been introduced, which is associated with body image dissatisfaction and weight and shape control behaviors. The Physical Appearance Perfectionism Scale (PAPS) is a 12-item 2-factor instrument developed to assess this new dimension of perfectionism. The aim of the study is to validate the Spanish version of PAPS among a representative sample of 850 male university students in Spain. Several psychometric analyses have been carried out: exploratory and confirmatory factorial structure, internal consistency, convergent and concurrent validity. Results showed that the Spanish version of the PAPS maintains the original factor structure with all items and proves to be a reliable instrument. Physical appearance-oriented perfectionism is associated with general perfectionism construct, with higher body dissatisfaction, ED and MD symptomatology, and the presence of compulsive exercise.